THE PRESENTATION OF INSTALLMENT TRANSACTIONS. - Pye, Malcolm L. (The Accounting Review, 1953)
Abstract The presentation of the subject of installment accounting, if guided by the material of many texts, is a difficult task which too often leaves the student, at least the average student, confused. This confusion arises from the obscure relationship between the procedures and the objectives. This relationship is obscure because the usual procedures approach the objectives in a round-about fashion, and have no apparent similarity to material already mastered by the student. When the students have reached the level where installment accounting is studied, they are sensitive to procedures, for so many tests have stressed journal entries, adjusting entries, and computations. Since the procedures of accounting for installment transactions appear to differ so radically from those of ordinary transactions, the student feels that the subject matter is foreign to other accounting topics. Instruction in installment accounting should emphasize income determination, but because of procedural difficulties, stress has too often been placed on the journal entries. By following familiar patterns, procedures will be clarified and stress can be placed on the recognition of income and the circumstances existing in various businesses which serve as dues for the recognition of income.